ANALISIS KOMPARASI NILAI PASAR INDUSTRI DI BURSA EFEK INDONESIA SELAMA PANDEMI COVID-19 - Rudy Syafariansyah Dachlan; Dian Irma Aprianti (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2022)
This study was conducted to analyze the comparison of the market value ratios of industries listed on the IDX during the COVID-19 Q1-Q4 2020 and Q1 2021. Comparative descriptive analysis method was used. The analysis used is the market value ratio. Descriptive statistical techniques discuss how to collect data, simplify numbers and comparative analysis methods explain how the results of comparisons and performance appraisals use market value ratios. The market value ratio variables used are EPS, PER and PBV. Based on the results of the analysis and discussion, it can be seen that there is an increase and decrease in the market value ratio in each industry. From the comparison, it can be stated that the consumer goods industry sector has a better market value ratio than other industrial sectors and the agricultural industry sector has a lower market value ratio than other industries.